An exploratory analysis of variations in quiet eye duration within and between levels of expertise - Chia, S. J.; Chow, J. Y.; Kawabata, M.; Dicks, M.; Lee, M. (International Journal of Sport and Exercise Psychology, 2017)
The ability to pick-up task-relevant visual information during movement control is crucial in successful sport performance. Quiet eye (QE), the final fixation prior to final movement onset, has been shown to be characteristic of the visual search strategies exhibited by skilled athletes in self-paced aiming tasks. Longer QE durations were previously associated with skill and successful performance outcomes. In this study, gaze behaviour data of six expert (E) and six novice (N) 10-pin bowlers were measured using a mobile eye tracker as they completed 20 trials of two single-pin conditions each (Easy: 1-pin; Hard: 10-pin). Expert bowlers exhibited significantly longer QE durations in both conditions as compared to their less-skilled counterparts. However, QE duration was not found to be significantly different as a function of accuracy nor task condition. Further detailed analysis revealed considerable variance in QE characteristics between individuals, warranting the need to explore individualised interventions centred on the development of perceptual-motor control during self-paced aiming tasks. Moreover, this study raised an important methodological issue relating to the analysis of trials with the absence of QE.